Interest on cash, fundamental value process and bubble formation on experimental asset markets - Giovanni Giusti; Janet Hua Jiang; Yiping Xu (Bank of Canada, 2014)
We study the formation of price bubbles on experimental asset markets where cash earns interest. There are two main conclusions. The first is that paying positive interest on cash is ineffective in diminishing bubbles through the reducing-active-participation channel. The second is that the fundamental value generating process plays a critical role in the formation of asset bubbles in the laboratory. In particular, bubbles tend to occur whenever there is a conflict between the sign of the time trend of the fundamental value and the sign of the expected dividend payment. This explanation is consistent with all existing studies that analyze the role of fundamental value processes in inducing bubbles on experimental asset markets. – – Nous étudions la formation des bulles de prix sur des marchés d'actifs expérimentaux au sein desquels les liquidités permettent de toucher un intérêt. Nous parvenons à deux conclusions principales. Premièrement, le fait d'appliquer un taux d'intérêt positif aux liquidités n'aide pas à diminuer les bulles par la réduction de la participation active aux marchés. Deuxièmement, dans le cadre expérimental, le processus de création de la valeur fondamentale joue un rôle essentiel dans la formation des bulles d'actifs. En particulier, les bulles ont tendance à surgir lorsque la tendance temporelle de la valeur fondamentale et le paiement de dividendes attendu sont de sens contraire. Cette explication est corroborée par toutes les études existantes qui analysent l'incidence du processus de création de la valeur fondamentale sur l'apparition de bulles dans les marchés d'actifs expérimentaux.
Keywords: C90; G10; 330; Asset pricing; Financial markets; Financial stability